Organisasi Kerja Sama Islam Menurut Perspektif Hukum Internasional: Sikap Dan Kontribusi Dalam Dua Dekade Terakhir - Firdaus Muhamad Iqbal (Intellectual Law Review (ILRE), 2023)
The Organization of Islamic Cooperation (OIC) was founded in 1969 through the Islamic Summit in Rabat as a response to the burning of the Al-Aqsa Mosque in Jerusalem and consists of 57 member countries. The aim of this research is to provide additional information about the OIC as a subject of international law, the main tasks and functions of the OIC, as well as the outlook and contributions of the OIC in the last two decades. This study employs a normative-juridical method with literature studies and a historical approach. The results of this study analyze three things: first, the historical background of the birth and development of the OIC. Second, the OIC as a subject of international law has personality rights and obligations according to international law. Third, outlook and contributions of the OIC have been shaped by holding two major meetings, namely the Extraordinary Summit and the Islamic Summit for the past two decades and producing legal instruments, namely resolutions and declarations which are sources of international law and become tools in solving a problem.